2020
DOI: 10.1029/2019gl086562
|View full text |Cite
|
Sign up to set email alerts
|

Global K‐Pg Layer Deposited From a Dust Cloud

Abstract: Although it is widely agreed that the distal K‐Pg clay layer contains ejecta from the Chicxulub impact site, no current models can explain how these ejecta travel from the impact site around the globe. A widely accepted hypothesis is that impact spherules and shocked minerals in the layer were ejected from an expanding impact plume and traveled to their final destination on a ballistic path. Shocked minerals, however, are ejected at too low a velocity to reach distal sites, and plausible ballistic ejection mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…Prolonged impact winter, cessation of photosynthesis, and perhaps acid rain resulting from release of SO 2 from evaporite sulfates (Alvarez et al, 1980; Artemieva & Morgan, 2017; Brugger et al, 2017; Gulick et al, 2019; Kring, 2007; Prinn & Fegley, 1987; Tabor et al, 2020; Toon et al, 1982; Vellekoop et al, 2014) were likely major killing mechanisms on land and in the oceans. These effects may have been enhanced by soot released by wildfires (Tschudy et al, 1984; Wolbach et al, 1990) and combusted target rock hydrocarbons (Kaiho et al, 2016; Lyons et al, 2020), and carbonate dust (Artemieva & Morgan, 2020), though this latter material has not been identified in boundary deposits. The impact occurred either between eruptive phases of the Deccan traps (Schoene et al, 2019), or largely before these phases (Sprain et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged impact winter, cessation of photosynthesis, and perhaps acid rain resulting from release of SO 2 from evaporite sulfates (Alvarez et al, 1980; Artemieva & Morgan, 2017; Brugger et al, 2017; Gulick et al, 2019; Kring, 2007; Prinn & Fegley, 1987; Tabor et al, 2020; Toon et al, 1982; Vellekoop et al, 2014) were likely major killing mechanisms on land and in the oceans. These effects may have been enhanced by soot released by wildfires (Tschudy et al, 1984; Wolbach et al, 1990) and combusted target rock hydrocarbons (Kaiho et al, 2016; Lyons et al, 2020), and carbonate dust (Artemieva & Morgan, 2020), though this latter material has not been identified in boundary deposits. The impact occurred either between eruptive phases of the Deccan traps (Schoene et al, 2019), or largely before these phases (Sprain et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 ‐related warming from these eruptions was either over (Hull et al, 2020) or served as a minor mitigating factor (Chiarenza et al, 2020). The effects of the impact are, however, directly tied to the mass extinction event (Artemieva & Morgan, 2017, 2020; Gulick et al, 2019; Schulte et al, 2010). Once formed, impact craters such as Chicxulub can provide unique habitats for life (Cockell et al, 2003; Russell & Hall, 2006), a function that may also have been in operation early in Earth history (Russell & Hall, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Dinosaurs were the most conspicuous members of late Mesozoic terrestrial ecosystems until the impact of an approximately 10 km wide meteorite caused the extinction of all non-avian dinosaur taxa 66 million years ago (Ma) [ 1 4 ]. The effects of this event were globally devastating and were caused by an ejecta blanket of dust and debris that encircled the Earth and cooled global temperatures by up to 10°C for decades, alongside the more immediate effects of wildfires and tsunamis in areas proximal to the impact [ 2 , 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…globally devastating and were caused by an ejecta blanket of dust and debris that encircled the Earth and cooled global temperatures by up to 10°C for decades, alongside the more immediate effects of wildfires and tsunamis in areas proximal to the impact [2,[5][6][7].…”
mentioning
confidence: 99%
“…Various other types of impact ejecta have been recovered from K-Pg event deposits, including impact spherules, some of which contain Ni-rich spinel crystals, and shocked mineral grains ( 5 , 6 , 11 ). While an assortment of HSE carrier phases has been identified within the boundary clay (including magnesioferrite crystals or other spinel group minerals, microkrystite impact spherules, organic matter, or iron-rich nanophases), Ir and the other siderophile elements were likely transported from the impact site across the globe within airborne microscopic dust and impact vapor condensates ( 1 , 11 , 12 ). The extraterrestrial matter found in the boundary layer was determined to be of carbonaceous chondritic composition ( 7 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%